APRIL limits atherosclerosis by binding to heparan sulfate proteoglycans - Tsiantoulas, Dimitrios; Eslami, Mahya; Obermayer, Georg; Clement, Marc; Smeets, Diede; Mayer, Florian J.; Kiss, Máté G.; Enders, Lennart; Weißer, Juliane; Göderle, Laura; Lambert, Jordi; Frommlet, Florian; et al. (Nature, 2021)
Atherosclerotic cardiovascular disease causes heart attacks and strokes, which are the leading causes of mortality worldwide1. The formation of atherosclerotic plaques is initiated when low-density lipoproteins bind to heparan-sulfate proteoglycans (HSPGs)2 and become trapped in the subendothelial space of large and medium size arteries, which leads to chronic inflammation and remodelling of the artery wall2. A proliferation-inducing ligand (APRIL) is a cytokine that binds to HSPGs3, but the physiology of this interaction is largely unknown. Here we show that genetic ablation or antibody-mediated depletion of APRIL aggravates atherosclerosis in mice. Mechanistically, we demonstrate that APRIL confers atheroprotection by binding to heparan sulfate chains of heparan-sulfate proteoglycan 2 (HSPG2), which limits the retention of low-density lipoproteins, accumulation of macrophages and formation of necrotic cores. Indeed, antibody-mediated depletion of APRIL in mice expressing heparan sulfate-deficient HSPG2 had no effect on the development of atherosclerosis. Treatment with a specific anti-APRIL antibody that promotes the binding of APRIL to HSPGs reduced experimental atherosclerosis. Furthermore, the serum levels of a form of human APRIL protein that binds to HSPGs, which we termed non-canonical APRIL (nc-APRIL), are associated independently of traditional risk factors with long-term cardiovascular mortality in patients with atherosclerosis. Our data reveal properties of APRIL that have broad pathophysiological implications for vascular homeostasis.